2012
DOI: 10.1371/journal.pone.0039875
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Infection Facilitates Invasion of Staphylococcus aureus into the Nasal Mucosa and Nasal Polyp Tissue

Abstract: Background Staphylococcus aureus ( S. aureus ) plays an important role in the pathogenesis of severe chronic airway disease, such as nasal polyps. However the mechanisms underlying the initiation of damage and/or invasion of the nasal mucosa by S. aureus are not clearly understood. The aim of this study was to investigate the interaction between S. aureus and herpes simplex virus type 1 (HSV1) in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 51 publications
0
38
0
1
Order By: Relevance
“…Another possible contributing factor to invasion of S. aureus could be pre-infection with herpes simplex virus type 1 (HSV1). Wang et al showed evidence suggestive of a significant damage to the nasal epithelium by HSV1 infection that could consequently facilitate invasion of S. aureus into the nasal mucosa [71]. …”
Section: Role Of S Aureus In Crsmentioning
confidence: 99%
“…Another possible contributing factor to invasion of S. aureus could be pre-infection with herpes simplex virus type 1 (HSV1). Wang et al showed evidence suggestive of a significant damage to the nasal epithelium by HSV1 infection that could consequently facilitate invasion of S. aureus into the nasal mucosa [71]. …”
Section: Role Of S Aureus In Crsmentioning
confidence: 99%
“…[2][3][4] It has been suggested that viral respiratory tract infection (VRI) influences the development or progressive course of CRS through various means. 5,6 In vitro studies demonstrated that VRIs can damage the epithelial cells covering the sinonasal cavity, resulting in dysfunction of the epithelial barrier and increased bacterial adhesion. 5,6 The interferon response of airway epithelial cells is critical for defense against viral infection because it is required to suppress viral replication.…”
mentioning
confidence: 99%
“…Conversely, the exposure of H. influenzae to primary human epithelial cells significantly enhanced the binding of HRV16, probably through the up-regulation of intercellular adhesion molecule and toll-like receptor-3 expression (89). Our recent study also showed that herpes simplex virus type 1 infection facilitates the invasion of S. aureus into the nasal mucosa and CRSwNP tissue (90). In humans with acute respiratory illnesses, however, children with HRSV and Mycoplasma pneumonia co-infection had more severe airway inflammation than those with HRSV infection alone (91); bacteria (influenzae, catarrhalis, and pneumoniae) are more likely to be detected among virusnegative specimens compared to virus-positive burden (92).…”
Section: The Interaction Between Virus and Bacteriamentioning
confidence: 71%